Le Jugement dernier de Léon Delmont : déplacements du sacré dans La Modification de Michel Butor - Guermès, Sophie (Quêtes littéraires, 2013)
The compartment in A Change of Heart is a secular space. However, the Sacred will gradually invade it through hallucinations of the narrator. Thus an unexpected and fantastic struggle led by the Pope, priests, cardinals, prophets and sibyls against Leon Delmont will cause a change of his initial decision, motivating and justifying the novel’s title.